Current Status of Technological Innovation Cluster Research - Wenjin Zhu (Journal of World Economy, 2023)
The research on innovation clusters has become the focus of academic research and scientific and technological decision-making of governments around the world. The construction of innovation clusters is of great significance to cultivate strategic emerging industries, enhance regional innovation capacity and promote the transformation of economic development mode. However, at present, the theoretical research on technological innovation clusters is not deep enough, and the theoretical framework is still not clear. On the basis of literature research, this paper starts with the concept of innovation cluster, associates it with technology cluster, and jointly introduces the origin and concept of technology innovation cluster. Based on the analysis of various literature, the shortcomings of the current research on technology innovation cluster and the direction of the next research are pointed out.